A Descriptive Study of Plant Physiology Practicum Activities - Yaumil Istiqlal M Nur; Hendra Yulisman; Diyyan Marneli; Nazar Muhammad (Integrated Science Education Journal, 2025)
Purpose of the study: This study aims to describe the practicum activities carried out in the Plant Physiology practicum activities of the Biology Education Tadris Laboratory, IAIN Batusangkar. Methodology: This descriptive study combines the accuracy of numerical data and a more profound understanding through observation and interviews. The population in this study were all students who took the plant physiology practicum course in the odd semester of 2019, totaling 96 people and six laboratory assistants. Data collection consisted of quantitative data collection using questionnaires and qualitative data through interviews and observations. Quantitative data analysis was carried out using the average percentage score for each activity. Furthermore, qualitative data analysis from observations and interviews was carried out by bringing up themes and information patterns from practicum activities to support quantitative data. Main Findings: Data analysis indicates that the practicum activities have been executed efficiently, evidenced by a planning score of 80.56 and an implementation score of 79.42. Additionally, the score for follow-up activity was 93.66. The overall average percentage of practicum activity execution was 84.55, indicating good category. Novelty/Originality of this study: The activities of the practicum are detailed in this article, including planning, implementation, and follow-up. In order to generate comprehensive data, the analysis employs descriptive methods that are supplemented by observational data. Research data was collected from all parties involved in the practicum activities, including students, practicum assistants, and laboratory assistants. In contrast to other researchers who exclusively employ qualitative data with samples of practicum participants.